Distributed coordinated tracking control of multiple unmanned surface vehicles under complex marine environments. (1st June 2020) - Liang, Xiao; Qu, Xingru; Hou, Yuanhang; Li, Ye; Zhang, Rubo
Abstract: In this paper, a coordinated tracking strategy with swarm center identification, self-organized aggregation, collision avoidance and distributed controller design for multiple unmanned surface vehicles (USVs) under complex marine environments including both unknown dynamics and external disturbances is presented. For self-organized aggregation and collision avoidance, a velocity feedback control with the repulsive potential function is employed for each vehicle to match surge velocity and heading angle with its neighbors. To keep all vehicles connected in a group, a virtual swarm center (SC) is simultaneously designed and identified using a consensus algorithm, thereby USVs have global knowledge of the desired trajectory. Aiming to precisely estimate completely unknown dynamics together with external disturbances, a distributed tracking controller based wavelet neural network (WNN) is further proposed within the coordinated tracking strategy. Simulation studies and comprehensive comparisons with conventional NN demonstrate excellent performance of the swarm tracking strategy and superiority of WNN scheme. Highlights: Coordinated tracking for unmanned surface vehicles is researched. Swarm strategy presents flexibility and applicability. Swarm center is identified. Distributed anti-disturbance controllers are employed. Six vehicles managed to be controlled without collision.